Absence of airway inflammation in a large proportion of adolescents with asthma. Issue 3 (22nd December 2015) - Brooks, Collin R.; van Dalen, Christine J.; Zacharasiewicz, Angela; Simpson, Jodie L.; Harper, Jacquie L.; Le Gros, Graham; Gibson, Peter G.; Pearce, Neil; Douwes, Jeroen
Abstract: Background and objective: Neutrophilic inflammation has been implicated in non‐eosinophilic asthma (NEA) in adults, but little is known about NEA in children/adolescents. We assessed clinical and inflammatory characteristics of NEA in adolescent asthma. Methods: Airway inflammation, sputum endotoxin, airway hyper‐reactivity, atopy and lung function were assessed in 77 adolescents with asthma and 68 without asthma (12–17 years). Asthma was identified on the basis of wheeze and asthma history. Results: The proportion of NEA (sputum eosinophils <2.5%) was 54%. In this group, atopy, sputum neutrophil, eosinophil, eosinophil cationic protein (ECP), endotoxin, neutrophil elastase and IL‐8 levels were not different from those without asthma. In contrast, eosinophilic asthma (EA) was associated with atopy and sputum ECP and IL‐8. The majority of NEA had no evidence of inflammation; only 14% had neutrophilia (≥61% neutrophils), compared with 11% of EA, and 15% of those without asthma. Small differences in FEV1 (NS) were found between EA and NEA, but symptom prevalence and severity was not different (63% of EA and 52% of NEA were classified moderate to severe). Conclusion: NEA is common in adolescent asthma and has similar clinical characteristics as EA. Neutrophils do not appear to play a role in NEA in adolescents, and underlying mechanisms may not involve airway inflammation. Abstract : Our study suggests that many adolescents with stable asthma do not appear to correspond to the conventional notion that asthma is 'an inflammatory disorder of the airways'. In the absence of overt inflammation, the mechanisms responsible for asthma symptoms in a large proportion of adolescent with asthma remain unknown.